VERIFICATION OF THE HYGIENIC SANITARY CONDITIONS OF FOOD STREET VENDING AND THE PROFILE OF VENDORS IN THE CITIES OF SÃO PAULO, SANTOS AND EMBU DAS ARTES (Fiep Bulletin - online, 2014)
The consumption of food on the street sold by vendors may offer high risk to public health in Brazil, considering these vendors usually don't possess much knowledge of irreprehensible hygiene and manipulation of foods. Objective: To verify the hygienic sanitary conditions of street vending, as well as the profile of street vendors, their personal hygiene and the hygiene of the place where the food stands are. Method: It relates to a quantitative, transversal, descriptive study, in which 90 street vendors have agreed to take part on the research, answering a form, containing objective questions based on the Resolutions RDC n. 218 and RDC n. 216 that were used as variables in the study composition. The data, after gathered, was presented in tables and simple frequency graphics expressed in numbers and percentages. The ethic aspects were respected, according to Resolution n. 196/96 (CNS-MS). Results: It was observed that 26% of the vendors age from 28 to 39 years old, 33% had a High School degree; 64% with family income from 2 to 5 minimum wages a month; 41% used the bus to get to their work location; 53% prepared the food at the location; 59% handled money and food with bear hands; 23% were located next to manholes. The obtained results suggest vendors don't possess knowledge about hygiene to work in the food business, because of the several irregularities observed relating to work location, handling, storage, transportation, and solid residue produced. The absence of frequent severe inspection, as well as the permissiveness of this business, seems to explain these flaws.
Keywords: Food on the street; Public Health; personal Hygiene